2017
DOI: 10.21608/zumj.2017.4443
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Social Marketing Campaign on Utilization of Primary Health Care Curative Services in Urban Sector of Sharkia Governorate

Abstract: Background: Primary Health Care (PHC) services underutilization was the main finding all over Egypt including Sharkia Governorate and social marketing campaign was a successful method to promote the use of such services. Aim & Objectives: The aim of this work is to maximize the utilization of PHC curative services with the following objectives: (1) to design and implement a tailored social marketing campaign in an urban area in Sharkia Governorate.(2) to assess the effect of this campaign on the rate of utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…The social marketing campaign was able to increase the flow number of the new patients attending FMC, the number of new family files opened and the frequency of weekly visits of regular attenders post-campaign than its number precampaign this is similar to Ghobashi et al, 2013 who concluded that service output indicators after social marketing campaign had improved and become more than before the campaign [11].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The social marketing campaign was able to increase the flow number of the new patients attending FMC, the number of new family files opened and the frequency of weekly visits of regular attenders post-campaign than its number precampaign this is similar to Ghobashi et al, 2013 who concluded that service output indicators after social marketing campaign had improved and become more than before the campaign [11].…”
Section: Discussionsupporting
confidence: 58%
“…A structured anonymous questionnaire [11] was used to obtain the data from the clinic's non/partial attendees who never came to the FMC or coming irregularly (once every 3 months) to find the causes of underutilization of clinics services.…”
mentioning
confidence: 99%